Ignition and combustion of liquid hydrocarbon droplets in premixed fuel/air mixtures at elevated pressures and temperatures - Bhoite, Siddhesh Bharat, author; Windom, Bret, advisor; Marchese, Anthony J., advisor; Olsen, Daniel B., committee member; Venayagamoorthy, Karan, committee member (Colorado State University. Libraries, 2022)
The combustion of two fuels with disparate reactivity such as natural gas and diesel in internal combustion engines has the potential to increase fuel efficiency, reduce fuel costs and reduce pollutant formation in comparison to traditional diesel or spark-ignited engines. However, dual-fuel engines are presently constrained by uncontrolled fast combustion (i.e., engine knock) as well as incomplete combustion and a better understanding of dual-fuel combustion processes is necessary to overcome these challenges. In addition to dual-fuel engines, this work is also motivated by abnormal combustion phenomenon that has been observed in highly boosted, spark ignited, natural gas engines, which is caused by engine lubricant oil droplets entering the cylinder and serving as unwanted ignition sources for the natural gas/air mixture. To study the fundamental combustion processes of ignition and flame propagation in dual-fuel engines and abnormal combustion triggered by lubricant oil droplets, single isolated liquid hydrocarbon droplets were injected into premixed CH4/O2/Inert mixtures at elevated temperatures and pressures. In this research, a rapid compression machine (RCM) was used in combination with a newly developed piezoelectric droplet injection system that is capable of injecting single liquid hydrocarbon droplets of 40 to 500 μm along the stagnation plane of the RCM combustion chamber. A high-speed Schlieren optical setup was used for imaging the combustion events in the chamber. Experiments were conducted for diesel fuel and lubricant oil droplets at various initial diameters (50 μm < do < 500 μm), various CH4/O2/Inert equivalence ratios (0 < ϕ < 1.2) and various compressed temperatures (740 K < Tc < 1000 K). Dual fuel experiments revealed multiple modes of droplet ignition, droplet combustion, and premixed flame propagation, which depend on the initial droplet temperature, droplet diameter, droplet velocity, and stoichiometry of the CH4/O2/N2/Ar mixture. In the case of small droplets, spherical ignition events were observed that transition into spherical non-premixed flames that envelope the droplet, producing an outwardly propagating spherical premixed flame. For larger droplet diameters moving at moderate velocity, the ignition event occurs near the droplet surface on the leeward side of the droplet and subsequently creates a non-premixed flame that envelopes the droplet and a non-spherical premixed flame. For droplets moving with high velocities, the ignition event occurs in the wake of the droplet, multiple diameters from the droplet surface, and creates a flame that propagates toward the droplet. Spherical, outwardly propagating premixed flames were observed for diesel droplet ignition in stoichiometric CH4/O2/N2/Ar mixtures, whereas elongated premixed flames were observed in lean CH4/O2/N2/Ar mixtures. The experiments conducted to understand abnormal combustion caused by lubricant oil droplets provided a valuable dataset of ignition delay periods of various petroleum and ester-based lubricant oils at a wide range of thermodynamic and mixture conditions. In concert with the experiments, a combined analytical droplet evaporation model and computational combustion model were developed that simulate the evaporation, ignition, and combustion processes observed in the experiments. The ignition delay dataset was used to successfully develop and validate a surrogate chemical kinetic mechanism suitable for mimicking the ignition characteristics of different lubricant oils. The experiments also revealed the different thermodynamic and mixture conditions at which the lubricant oil droplets did not show ignition. At compressed pressure of 24 bar and varied compressed temperatures of 740 K < Tc < 900 K in CH4/O2/N2/Ar mixture of ϕ = 0.6, two ester-based oils (EBO3 and EBO4) showed no ignition. The experiments and modeling indicate the minimum and maximum droplet sizes for which ignition will occur, the location and mode of ignition in the vicinity of the liquid droplet and the conditions under which the ignition event will transition into a propagating premixed flame. These experimental observations further enhance our understanding of lubricant oil combustion and provide qualitative information of engine operating conditions which can lower the abnormal combustion occurrence in natural gas engines. The results of this study advance the fundamental understanding of dual fuel combustion and provide the practical knowledge to inform which lubricant oil types and droplet sizes promote or inhibit abnormal combustion in natural gas engines.